Gasotransmitters in pregnancy: from conception to uterine involution†. Issue 1 (8th March 2019) - Guerra, Damian D; Hurt, K Joseph
Abstract: Gasotransmitters are endogenous small gaseous messengers exemplified by nitric ox ide (NO), carbon monoxide (CO), and hydrogen sulfide (H2 S or sulfide). Gasotransmitters are implicated in myriad physiologic functions including many aspects of reproduction. Our objective was to comprehensively review basic mechanisms and functions of gasotransmitters during pregnancy from conception to uterine involution and highlight future research opportunities. We searched PubMed and Web of Science databases using combinations of keywords nitric oxide, carbon monoxide, sulfide, placenta, uterus, labor, and pregnancy. We included English language publications on human and animal studies from any date through August 2018 and retained basic and translational articles with relevant original findings. All gasotransmitters activate cGMP signaling. NO and sulfide also covalently modify target protein cysteines. Protein kinases and ion channels transduce gasotransmitter signals, and co-expressed gasotransmitters can be synergistic or antagonistic depending on cell type. Gasotransmitters influence tubal transit, placentation, cervical remodeling, and myometrial contractility. NO, CO, and sulfide dilate resistance vessels, suppress inflammation, and relax myometrium to promote uterine quiescence and normal placentation. Cervical remodeling and rupture of fetal membranes coincide with enhanced oxidation and altered gasotransmitter metabolism. Mechanisms mediating cellular and organismal changes in pregnancy due to gasotransmitters are largely unknown. Altered gasotransmitter signaling has been reported for preeclampsia, intrauterine growth restriction, premature rupture of membranes, and preterm labor. However, in most cases specific molecular changes are not yet characterized. Nonclassical signaling pathways and the crosstalk among gasotransmitters are emerging investigation topics. Abstract : Gasotransmitters modulate mammalian pregnancy via conserved ion channels, receptors, and second messenger-mediated signal transduction pathways.